African histories of the Internet. Issue 1 (2nd January 2017) - Wasserman, Herman
ABSTRACT: This article explores the notion of Internet histories and associated digital cultures from an African point of view. It argues that histories of the Internet in Africa would need to be heterogeneous, multi-level and flexible, especially given the various platforms and applications through which the Internet is accessed and used on the continent. The article provides an overview of the major areas of research into the Internet in the Global South and Africa in particular, and makes suggestions for how these areas could inform a historiography of the Internet in Africa.